Evaluation of Sustainability Supply Chain Performance in the Food Industry: A Case Study - Danang Kumara Hadi; Andika Putra Setiawan; Oppy Valencia Indrian; Erwin Fadilatur Rosyid (Department Industrial Engineering, University of Muhammadiyah Malang, 2023)
Evaluating sustainability in the food supply chain has multiple benefits, including reducing environmental impact, meeting regulations, satisfying consumer demands, improving efficiency, and enhancing business reputation. This paper outlines a Sustainability Supply Chain Management (SSCM) framework using the Analytic Hierarchy Process (AHP) to weigh Key Performance Indicators (KPIs). With 12 variables and 39 KPIs, the method involves data collection, performance measure selection, and analysis. KPIs with lower weight values highlight areas needing improvement, such as recycling costs, personnel expenses, sales responsiveness, eco-friendly labelling, distribution efficiency, green product development, recycled material usage, employee capabilities, product reputation, worker satisfaction, and stakeholder trust. Based on KPI weights, recommendations include prioritizing energy use in production and marketing, ensuring timely product delivery, maintaining product quality, streamlining production processes, focusing on energy efficiency, promoting eco-labelling, fostering eco-awareness, and advancing environmental technology.